2014
DOI: 10.1074/jbc.m114.576033
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Mutants in Chaperonin Proteins CCT4 and CCT5 Associated with Hereditary Sensory Neuropathy

Abstract: Background: Point mutations in two genes encoding chaperonin subunits have been implicated in neuropathies. Results: CCT4 and CCT5 proteins carrying these mutations were expressed in bacteria and investigated for their biochemical defects. Conclusion: H147R CCT5 is faulty in chaperoning function, whereas C450Y CCT4 may be defective in protein stability. Significance: These biochemical defects may be the source of these neuropathies in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 40 publications
3
42
0
Order By: Relevance
“…Confirming the previous fibril formation and aggregation observations with a new mHTT construct further solidifies these findings. Moreover, the synthetic chaperonin-like CCT5 complex, which has been shown recently to also inhibit mHTT aggregation (24), was structurally characterized to provide information on its mechanism of interaction with mHTT. As shown previously, it is possible to overexpress the CCT5 subunit in bacteria, producing the CCT5 complex (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Confirming the previous fibril formation and aggregation observations with a new mHTT construct further solidifies these findings. Moreover, the synthetic chaperonin-like CCT5 complex, which has been shown recently to also inhibit mHTT aggregation (24), was structurally characterized to provide information on its mechanism of interaction with mHTT. As shown previously, it is possible to overexpress the CCT5 subunit in bacteria, producing the CCT5 complex (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the synthetic chaperonin-like CCT5 complex, which has been shown recently to also inhibit mHTT aggregation (24), was structurally characterized to provide information on its mechanism of interaction with mHTT. As shown previously, it is possible to overexpress the CCT5 subunit in bacteria, producing the CCT5 complex (23,24). It is intriguing to raise the question of whether CCT5, as a homooligomer complex, is native to mammalian cells, which awaits future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, the use of the archaeal chaperonin provided information that reflects the anomalies of the human mutant CCT5, which has been studied in vitro (Sergeeva et al, 2014). In a pioneering study, the human CCT4, and CCT5 subunits have been shown to form homohexadecamer complexes after expression of the subunits in E. coli (Sergeeva et al, 2013).…”
Section: The Thermosome Of Pyrococcus Furiosusmentioning
confidence: 99%